The Longmire defense - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery, 2023)
"Walt Longmire faces one of his most challenging crime scenes as he tries to reckon with the revelations of his last case where he confronted the ghosts of his past and questioned the very nature of justice and mercy in the hard country of the West. Deepin the heart of the Wyoming countryside, Sheriff of Absaroka County, Walt Longmire, is called to a crime scene like few others that he has seen. This crime brings up issues that go back to Walt's grandfather's time in Wyoming, as the revelations he learnsabout his grandfather come back to offer clues and motives for Walt's investigation. Filled with back-country action, and with the great cast of characters that readers have come to love with the Longmire series, this new book will be sure to satisfy both long-time readers and those new to the series"--